Correction: Biofunctional Janus particles promote phagocytosis of tumor cells by macrophages. Issue 27 (1st July 2022) - Zhang, Ya-Ru; Luo, Jia-Qi; Li, Jia-Xian; Huang, Qiu-Yue; Shi, Xiao-Xiao; Huang, Yong-Cong; Leong, Kam W.; He, Wei-ling; Du, Jin-Zhi
Abstract : Correction for 'Biofunctional Janus particles promote phagocytosis of tumor cells by macrophages' by Ya-Ru Zhang et al., Chem. Sci., 2020, 11, 5323–5327, ; https://doi.org/10.1039/D0SC01146K .